Realizing a highly luminescent perovskite thin film by controlling the grain size and crystallinity through solvent vapour annealing - Chin, Sang Hyun; Choi, Jin Woo; Woo, Hee Chul; Kim, Jong H.; Lee, Hong Seok; Lee, Chang Lyoul (Nanoscale, 2019)
Organometallic halide perovskite films were treated with novel facile solvent vapour annealing to control crystal grain size as well as the crystallinity of perovskite. As both polarity and vapour pressure of the treatment solvent for perovskite increase, luminance increases and the wavelength of the photoluminescence emission peak decreases due to enhanced crystallinity and reduced grain size.
Keywords: Crystal grain size; Grain size; Halide perovskites; Perovskite thin films; Photoluminescence emission; Vapour pressures